Folk prescription for treating rhinitis as a rare cause of childhood lead poisoning: a case series - Xiao-Lan Ying; Morri Markowitz; Chong-Huai Yan (BMC, 2018)
Abstract Background Folk prescriptions continue to be important sources of childhood lead poisoning. Nasal spray folk prescriptions for treating rhinitis has only been reported once previously as a cause of lead poisoning. Case presentation We identified three pediatric cases of severe lead poisoning caused by nasal spray folk medicines prescribed for treating rhinitis. The three patients had similar clinical manifestations including: severe abdominal pain, headache, pale appearance and fatigue. Liver function tests were abnormal. Blood lead levels (BLLs) of the three patients were 91 μg/dL, 91 μg/dL, and 105 μg/dL, respectively. After chelation BLLs decreased. The lead content of the three folk remedies as measured by inductively coupled plasma mass spectrometry (ICP-MS) were 14.8, 22.3, and 33.4%. All the symptoms resolved during a course of chelation therapy. There were no severe side effects of treatment. Conclusions Nasal spray folk prescriptions for treating rhinitis may contain extremely high bio-accessible lead content and are potential sources of lead poisoning. Clinicians should be alert to this possibility especially in those children presenting with multisystem symptoms.